Sympathetic innervation is essential for metabolic homeostasis and pancreatic beta cell function in adult rats. (15th February 2018) - Prates, Kelly V.; de Oliveira, Júlio C.; Malta, Ananda; Matiusso, Camila C.I.; Miranda, Rosiane A.; Ribeiro, Tatiane A.; Francisco, Flávio A.; Franco, Claudinéia C.S.; Moreira, Veridiana M.; Alves, Vander S.; Torrezan, Rosana; Mathias, Paulo C.F.; et al.
Abstract: Obesity is associated with an imbalance in the activity of the autonomic nervous system (ANS), specifically in the organs involved in energy metabolism. The pancreatic islets are richly innervated by the ANS, which tunes the insulin release due to changes in energy demand. Therefore, changes in the sympathetic input that reach the pancreas can lead to metabolic dysfunctions. To evaluate the role of the sympathetic ends that innervate the pancreas, 60-day-old male Wistar rats were subjected to sympathectomy (SYM) or were sham-operated (SO). At 120 day-old SYM rats exhibited an increase in body weight, fat pads and metabolic dysfunctions. Decreases in the HOMA-IR and reductions in insulin release were observed both in vivo and in vitro . Furthermore, the SYM rats exhibited altered pancreatic islet function in both muscarinic and adrenergic assays and exhibited high protein expression of the alpha-2 adrenergic receptor (α2AR). Because α2AR has been linked to type 2 diabetes, these findings demonstrate the clinical implications of this study. Highlights: Sympathetic innervation, although later in life, is essential for the modulation of insulin release by pancreatic beta cells. Sympathetic denervation leads to the adaptation in both insulin release and insulin sensitivity. Overexpression in the α2AR reduces insulin release by pancreatic beta cells and increases the risk of type 2 diabetes. Dysfunction of sympathetic nervous system leads to altered response of insulin release in presence of muscarinic agonist. The perfect balance between the two branches of the autonomic nervous system is essential for metabolic homeostasis.